Correlation of visual acuity changes and optical coherence tomography imaging in patients with central retinal artery occlusion post-arterial thrombolysis - Weiwei Wang; Tao Lei; Runsheng Wang; Bo Zhang; Xiaotang Wang; Teng Ma (Scientific Reports)
Abstract This retrospective study investigates the correlation between visual acuity changes and structural modifications observed through optical coherence tomography (OCT) in patients with central retinal artery occlusion (CRAO) treated with urokinase. Conducted at the Neuro-Ophthalmology Center of Xi’an People’s Hospital from January 2022 to May 2023, the study included 217 CRAO patients (217 eyes), comprising 157 males and 60 females, aged 18 to 83 years (mean age: 57.8 ± 13.3 years). Key data were collected on visual acuity, ocular motility, and various imaging techniques at admission and post-thrombolysis. Results showed a significant improvement in visual acuity from 2.4 ± 0.5 to 1.9 ± 0.7 (P < 0.001) after treatment. Notably, patients with severe retinal damage had poorer visual recovery compared to those with milder damage. OCT analysis revealed a decrease in macular foveal retinal thickness from 415.5 ± 107.7 μm to 362.1 ± 93.8 μm (P < 0.001). Correlation analysis confirmed an association between visual acuity and retinal thickness (P < 0.001). Inter-observer variability for OCT grading was assessed using Cohen’s Kappa, which yielded a Kappa value of 0.873 (P < 0.001). This study underscores the relationship between visual recovery and retinal structural changes in CRAO patients, emphasizing the efficacy of urokinase treatment, particularly in mild to moderate cases, and the need for personalized therapeutic strategies based on condition severity.